SCIENTIFIC WRITING SKILL DAN ORAL COMMUNICATION SKILL PADA MAHASISWA PRODI PENDIDIKAN BIOLOGI FMIPA UNIVERSITAS NEGERI MALANG - Suwono, Hadi; Budi, Angga Hermana; Ramadani, Shefa Dwijayanti; Sukmawati, Ika (Jurnal Pendidikan Biologi, 2016)
The General Biology lecture on bilingual classes conducted by giving the assignment of preparing a summary of biology topics and then be presented and discussed. The analysis of the initial ability of students in scientific writing skills and oral communication skills were still low. The low level of both skills were reflected on the meaning and development aspects of the summary that were still in the beginner category (28%) and develop category (56%). Just as many (16%) of the students were in the category of competent and no students were included in the expert category. A similar picture is also seen in the organizational aspects of writing, language and structure of writing a summary. The observation of the oral communication skills of the students showed that the content and its delivery were still in the beginner category. This fact requires the effort to empower both these skills, since  that scientific writing skills and oral communication is an important skill of scientific literacy of students in 21st  century life. SRE (Sumarizing, Reviewing, and Evaluating) Writing Strategy is a learning strategy that could potentially improve both the skills. Effectiveness and optimization of the process of learning through the application of SRE empower the scientific writing skills and oral communication skills of students have learned through classroom action research-based lesson study. The improvement scientific writing skills and oral communication skills students in the research presented further